EARLY EMBRYONIC DEATH ASSOCIATED CHANGES IN STEROID HORMONES, LEPTIN, IGF-1, NITRIC OXIDE, ZINC AND COPPER IN MARES - MOHAMMAD, ASHA; KANDIEL, MMM; ABOU-EL-ROOS, MEA; EL AZAB, AI; ABO EL-MAATY, AM (The Indian Journal of Animal Reproduction, 2022)
Mares exhibting early embryonic death (EED, n=8), non-pregnancy (NP, n=12) and pregnancy (P, n=10) underwent ultrasound examination and blood sampling until week 4 post-breeding to assess the changes in reproductive and metabolic hormones, nitric oxide (NO), copper and zinc. Progesterone increased (p<0.05) and NO decreased (p<0.05) in P mares compared to EED and NP mares. Zinc (p≤0.05) at week 1, copper (p≤0.05) at week 2, and NO and copper (p<0.05), and estradiol and leptin (p≤0.05) at week 4 varied between NP, P and EED mares. The disturbance in ovarian and metabolic hormones concomitant with inflammatory mediators and/ or trace-elements might be responsible for EED in mares.